Diffractive Imaging of C60 Structural Deformations Induced by Intense Femtosecond Midinfrared Laser Fields - Fuest, Harald; Lai, Yu Hang; Blaga, Cosmin I.; Suzuki, Kazuma; Xu, Junliang; Rupp, Philipp; Li, Hui; Wnuk, Pawel; Agostini, Pierre; Yamazaki, Kaoru; Kanno, Manabu; Kono, Hirohiko; et al. (My University, 2019)
Theoretical studies indicated that C60 exposed to linearly polarized intense infrared pulses undergoes periodic cage structural distortions with typical periods around 100 fs (1 fs=10−15 s). Here, we use the laser-driven self-imaging electron diffraction technique, previously developed for atoms and small molecules, to measure laser-induced deformation of C60 in an intense 3.6 μm laser field. A prolate molecular elongation along the laser polarization axis is determined to be (6.1±1.4)% via both angular- and energy-resolved measurements of electrons that are released, driven back, and diffracted from the molecule within the same laser field. The observed deformation is confirmed by density functional theory simulations of nuclear dynamics on time-dependent adiabatic states and indicates a nonadiabatic excitation of the hg(1) prolate-oblate mode. The results demonstrate the applicability of laser-driven electron diffraction methods for studying macromolecular structural dynamics in four dimensions with atomic time and spatial resolutions.